Chemical Characteristics of Cascara, Coffee Cherry Tea, Made of Various Coffee Pulp Treatments. Issue 1 (March 2021) - Arpi, N; Muzaifa, M; Sulaiman, M I; Andini, R; Kesuma, S I
Abstract: Coffee cherry pulp contains caffeine, polyphenols and tannins which can cause environmental problems if discarded, but can be a potential source of antioxidants, phenolic compounds, and caffeine for functional drinks, like cascara. The chemical properties of cascara beverage from six different treatments of coffee cherry pulp were investigated. The pulp treatments were, P1 = pulp of coffee cherries which were kept in a sack for 12 hours before pulping (delayed pulping), P2 = pulp soaked in water for 12 hour, P3 = pulp left in a basket at room temperature for 12 hours, P4 = pulp/husk of dry process coffee, P5 = pulp of wet process coffee, P6 = pulp/husk of wine process coffee (prolonged dried coffee). The results show that the treatments did not affect the cascara beverage antioxidant activity which was between 53-78% DPPH inhibition. However, all treatments lowered tannin contents to about 35 mg/L, except for the P3 and P6 treatments. The cascara beverage caffeine content of P1, P2, and P3 treatments was low, around 0.20%, and about twice of that in the P4-P6 treatments. Cascara beverage of P4 contained the highest total acids and the lowest pH which was 4.18, whereas cascara tea/beverage of the wet process (P5 treatment) had high caffeine and low tannin contents with moderate pH and total acid content.